„Najciekawsza wydaje mi się właśnie osobność” (Charles Reznikoff i przekłady Piotra Sommera) - Orska, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The focus of this paper is the Polish translation of Charles Reznikoff poetry. Firstly, there goes an overall characteristic of the work by the American writer, whose conceptions became a core of the objectivist group-program of young poets connected to the Jewish diaspora in the 1930’s. Later, the main focus shifts to the conditions and presumable reasons for certain choices made by Piotr Sommer, Reznikoff’s Polish translator. Sommer’s choice – focusing predominantly on Reznikoff’s poetic miniatures – sheds light on the translator’s artistic preferences. Those poems by Reznikoff that have been translated into Polish do not carry as rich a historical, social, and cultural context – so important for an artist of the Jewish background – as his longer works, saturated with the religious allusions. However, Sommer’s translator’s craft – full of care and responsive to detail – allows his translations to frequently signal the strangeness and liminality of the passer-by subject, roaming the streets of New York.